2009
DOI: 10.1186/1471-2180-9-28
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a chemoattractant transcriptional response by a Campylobacter jejuni boiled cell extract in colonocytes

Abstract: BackgroundCampylobacter jejuni, the commonest cause of bacterial diarrhoea worldwide, can also induce colonic inflammation. To understand how a previously identified heat stable component contributes to pro-inflammatory responses we used microarray and real-time quantitative PCR to investigate the transcriptional response to a boiled cell extract of Campylobacter jejuni NCTC 11168.ResultsRNA was extracted from the human colonocyte line HCA-7 (clone 29) after incubation for 6 hours with Campylobacter jejuni boi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
5
1
Order By: Relevance
“…Thus, the commensal behavior of Campylobacter in porcine host could be explaining the lack of proinflammatory response observed in IPI-2I and IPEC-J2. Although the important role of molecules such as CCL2 and CXCL2 as potential regulators of monocyte recruitment and polymorphonuclear leukocytes in human campylobacteriosis has been described (Bakhiet et al, 2004;Mellits et al, 2009), our data show that CCL2 and CXCL2 mRNA expression were similar in human and porcine cells. Therefore, our results suggest that CCL2 and CXCL2 did not play an important role in early immune response against Campylobacter.…”
Section: Discussioncontrasting
confidence: 62%
“…Thus, the commensal behavior of Campylobacter in porcine host could be explaining the lack of proinflammatory response observed in IPI-2I and IPEC-J2. Although the important role of molecules such as CCL2 and CXCL2 as potential regulators of monocyte recruitment and polymorphonuclear leukocytes in human campylobacteriosis has been described (Bakhiet et al, 2004;Mellits et al, 2009), our data show that CCL2 and CXCL2 mRNA expression were similar in human and porcine cells. Therefore, our results suggest that CCL2 and CXCL2 did not play an important role in early immune response against Campylobacter.…”
Section: Discussioncontrasting
confidence: 62%
“…We chose to use HCA7 cells in preference to CaCo2 cells because they have a differentiated large rather than small bowel phenotype and because they are capable of expressing COX-2 under induction conditions. Our data suggest that this is an informative model and cell line to study disease pathogenesis and signaling mechanisms [40] .…”
Section: A B C D E Fmentioning
confidence: 79%
“…As yet it is uncertain whether intracellular invasion directly causes the associated release of IL-8 and PGE2, or whether this is a secondary consequence of cell death. A direct specific effect is possible since we have reported that IL-8 synthesis and PGE2 release from epithelial monolayers also occur in response to treatment with a boiled cell-free extract of C. jejuni [38] , with induction of COX-2 [39] and activation of nuclear factor-κB (NF-κB) and other relevant signaling pathways [40] . Enhanced release of IL-8 and other chemokines would play an important role in chemoattraction of neutrophils that characterizes some clinical infections with C. jejuni.…”
Section: A B C D E Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that CCL20 production and recruitment of CCR6+ DC occurs during infection in mucosal sites, such as the gut 20,41,42 and lung 43 . This migration and activation of mucosal DC has also been shown to be an important host strategy for the induction of pathogen-specific effector T cell responses 18,20 .…”
Section: Discussionmentioning
confidence: 99%